2016
DOI: 10.4103/0972-0707.173207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different final irrigating solutions on smear layer removal in apical third of root canal: A scanning electron microscope study

Abstract: Aim:The aim of this in vitro study is to compare the smear layer removal efficacy of different irrigating solutions at the apical third of the root canal.Materials and Methods:Forty human single-rooted mandibular premolar teeth were taken and decoronated to standardize the canal length to 14 mm. They were prepared by ProTaper rotary system to an apical preparation of file size F3. Prepared teeth were randomly divided into four groups (n = 10); saline (Group 1; negative control), ethylenediaminetetraacetic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…In the apical third, QMix more effectively removes smear layer than 17% EDTA and similar to MTAD. These results are in accordance with recent studies of Ballal et al (2016) and Vemuri et al (2016) showing superior effect of QMix in removing the smear layer in the apical third than that of EDTA. Lower smear layer capability of 17% EDTA in the apical root third has been shown in previous studies (Ballal, Kandian, Mala, Bhat, & Acharya, 2009;Mancini, Armellin, Casaglia, Cerroni, & Cianconi, 2009;Torabinejad et al, 2003 NOGO-ŽIVANOVI C ET AL.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the apical third, QMix more effectively removes smear layer than 17% EDTA and similar to MTAD. These results are in accordance with recent studies of Ballal et al (2016) and Vemuri et al (2016) showing superior effect of QMix in removing the smear layer in the apical third than that of EDTA. Lower smear layer capability of 17% EDTA in the apical root third has been shown in previous studies (Ballal, Kandian, Mala, Bhat, & Acharya, 2009;Mancini, Armellin, Casaglia, Cerroni, & Cianconi, 2009;Torabinejad et al, 2003 NOGO-ŽIVANOVI C ET AL.…”
Section: Discussionsupporting
confidence: 93%
“…The difference in the efficiency of the removal of the smear layer between MTAD, QMix, and 17% EDTA was examined in several previous studies. However, obtained results have not yet reached a unified conclusion on which irrigant solution was the most efficient (Ali Mozayeni, Hossein Javaheri, Poorroosta, Asna Ashari, & Hossein Javaheri, 2009;Dai et al, 2011;Eliot et al, 2014;Jardine et al, 2016;Stojicic, Shen, Qian, Johnson, & Haapasalo, 2012;Ulusoy & Görgül, 2013;Vemuri et al, 2016).…”
mentioning
confidence: 95%
“…[ 1 ] McComb and Smith were the first researchers to describe smear layer on the surface of instrumented root canal walls. [ 3 ] Smear layer from the dentinal tubules has the ability to protect the bacteria from irrigation or intracanal medicament thus avoiding complete disinfection of the infected canals and thorough sealing of the entire root canal system. [ 4 ] Thus, removal of smear layer from the root canal walls is highly necessary for long-standing endodontic success.…”
Section: Introductionmentioning
confidence: 99%
“…Eleven studies compared QMix to various irrigants like EDTA [ 23 24 25 26 27 28 29 30 31 33 35 ], 4 studies on MTAD [ 23 31 34 35 ], 5 studies on NaOCl [ 23 27 28 29 33 ], 2 studies on 7% EDTA (SmearClear) [ 30 32 ], 10% citric acid [ 29 33 ], one study on chitosan [ 32 ], glyde [ 32 ], 1% peracetic acid [ 33 ], Tubulicid Plus [ 34 ] and 7% maleic acid [ 28 ]. The effectiveness of smear layer removal was measured by different scoring systems.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that QMix removes smear layer more effectively than other irrigants whereas some results were contradictory. Thirteen studies have claimed that higher effectiveness was affected by the duration of QMix irrigation [ 23 24 25 26 27 28 29 30 31 32 33 34 35 ].…”
Section: Introductionmentioning
confidence: 99%